CHANGES IN CHINESE CULTURE IN THE CONTEXT OF GLOBALIZATION (Journal of Oriental Studies, 2025)
The article analyzes the changes in Chinese culture during the period of globalization, the impact of cultural reforms and global processes on culture and the trends of the revival of traditional culture. In the context of globalization, Chinese culture is undergoing significant changes that can contribute to the main aspects of society. Globalization, on the one hand, promotes the spread of Chinese cultural values, traditions and language outside the country, increasing its influence on the world stage. On the other hand, it leads to the interaction and mutual penetration of cultures, while it causes both the enrichment and the change of traditional elements of Chinese culture. The main purpose of studying the topic was to identify the problem of cultural diversity in the context of China's globalization and to consider the conditions for preserving its own traditional Chinese culture. The main objective of studying the topic is to identify the connection between traditional Chinese culture in modern China and the new ideology in government, contributing to the modernization of the country. This is due to the fact that the preservation and development of traditional Chinese culture has a positive impact on China's rapid economic growth. Diversity and unity of culture are two essential aspects of the development of cultural diversity in the modern world. Therefore, in the context of globalization, it is necessary not only to adhere to the principle of the unity of culture as a universal phenomenon, but also, based on the principle of preserving any particular culture, to increase resistance to cultural diversity, each of which affects the processes of globalization to varying degrees. This is the main novelty of the study- a complete study of China's cultural transformation in the process of globalization, which is developing by combining the concepts of cultural diversity and cultural unity. This is due to the fact that several factors influenced the change in Chinese culture. The most important aspect is digitization and social media, which have become a platform for promoting Chinese culture abroad. At the same time, there is a growing interest in cultural heritage within the country, which is reflected in the revival of traditional practices and their adaptation to modern conditions.Keywords: globalization, national identity, cultural exchange, digitalization, revolution.